Case Manager Experience in Health Services in Regional Hospitals in Bali - Susilayasa, I Komang Alit; Susanti, Ni Luh Putu Dina; Wahyuningsih, Luh Gde Nita Sri; Wulandari, Ida Ayu Putri (GLOBAL HEALTH SCIENCE GROUP, 2024)
The complexity of patient problems and service management involving multiple professions has the potential to cause patient safety problems. Hospitals need a design or strategy to be able to carry out service processes with a focus on improving service quality and patient satisfaction, namely case management. This research is to explain the case manager's perception of their role and function, describe the role and function of the case manager in implementing case management as well as obstacles in implementing case management in hospitals. Data was collected by conducting interviews with participants who met the inclusion criteria. There are five themes resulting from this research: helping to implement patient centered care, implementing case management in hospitals, first manager of quality control and controlling hospital costs, implementing case management in government hospitals still encountering obstacles. The perception of the role and function of the case manager is well known, the role and function in implementing case management is also quite good and there are still obstacles in implementation, namely from patients, initial screening in the room, hospital organizations, clinical leaders and case managers.